MEK inhibitors activate Wnt signalling and induce stem cell plasticity in colorectal cancer - Zhan, Tianzuo; Ambrosi, Giulia; Wandmacher, Anna Maxi; Betge, Johannes; Hinsenkamp, Isabel; Bamberg, Leonhard Valentin; Heßling, Bernd; Müller-Decker, Karin; Burgermeister, Elke; Ebert, Matthias; Boutros, Michael (Nature Communications, 2019)
Wnt signaling is necessary for colorectal cancer tumorigenesis and stem cell maintenance. Here, the authors identify MEK1/2 inhibitors as potent activators of Wnt/β-catenin signalling and show that clinically approved MEK inhibitors inadvertently induce stem cell plasticity in colorectal cancer.
Tianzuo Zhan, Giulia Ambrosi and Anna Maxi Wandmacher contributed equally
Gesehen am 28.06.2019